Teaching English through a bilingual learning ecosystem in the secondary vocational school of industrial technology - Rahmiani, Nur; Marwandi, Marwandi (Journal of Applied Studies in Language, 2022)
This research aims to examine the issue of bilingual learning ecosystems (BLE) in industry-based technology vocational schools. This study is interesting because it becomes an academic effort in overcoming learning difficulties in vocational school students, primarily in setting English learning time and mastering the particular skills of global competitive industrial technology. Using descriptive qualitative research that includes a series of observational data collection, interviews, and documentation, the authors discover the concept of BLE based on school perspective and BLE implementation in the learning process. This study concludes that BLE can be prepared in English and non-English courses by involving school biotic and abiotic elements through collaborative teaching. BLE also supports scientific integration in vocation learning at the secondary level, which has implications for increasing study hours and increasing enrichment of English material that is specific to industry technology vocation students outside of hours that have been scheduled. It is believed that BLE can support the achievement of enhancing English skills with specific goals as well.